The radical soft-tissue mobilization (Kelly repair) for bladder exstrophy. Issue 6 (December 2015) - Leclair, M.-D.; Villemagne, T.; Faraj, S.; Suply, E.
Summary: The radical soft-tissue mobilization (RSTM) technique has been proposed as an alternative for staged reconstruction of bladder exstrophy. In this video, we demonstrate the successive steps of this technique. Methods: A newborn male with classic bladder exstrophy underwent bladder closure without pelvic osteotomies at birth; he then underwent RSTM at 1 year of age. Technique: Mobilization : The RSTM involved simultaneous intra-pelvic and perineal dissection, aiming at full mobilization of potential urethral sphincter striated structures, levatores ani muscles, pudendal pedicles and corpora cavernosa from their attachment on the pubic bones. From the perineal approach, a periosteum incision was performed on the antero-medial aspect of the pubic bones, and the periosteum was peeled from the ischio-pubic ramus, lifting the corpora from the bone and providing control on the pudendal pedicles. The attachments of all striated muscular structures on the lower aspects of the posterior corpora (transverse perinei, bulbo-spongiosus, ischio-cavernosus muscles) were released to allow adequate re-approximation around the reconstructed urethra. Reconstruction : After ureteric reimplantation, a funnel-shaped cervicoplasty was performed and continued by urethroplasty over an 8-Fr catheter. The muscular structures mobilized from the corpora and the bones were wrapped around the neo-urethra, which was transposed ventrally in the scrotal position, creating a temporary hypospadiac urethrostomy. After abdominal wall closure, the corpora were then de-rotated, and secured to the neo-symphisis with non-absorbable sutures, and the penile skin shaft was reconstructed. Results: At the 12-month follow-up, the boy was asymptomatic, still in nappies, with non-dilated upper-tracts on renal ultrasound, and dryness intervals of 90 min. Conclusion: Radical soft-tissue mobilization allows a tension-free bladder-neck reconstruction, and may favour development of physiological continence mechanisms independent of the inevitable pubic symphisis re-enlargement. Creation of temporary hypospadias is most often needed to maximize penile length. This technically demanding procedure requires thorough knowledge of detailed anatomy of the bladder exstrophy pelvis, as demonstrated in this video.